Comparative numerical study on the child head injury under different child safety seat angles. Issue 4 (July 2019) - Razaghi, Reza; Biglari, Hasan; Hasani, Mojtaba; Karimi, Alireza
Highlights: Child safety seat (CSS) would dramatically diminish the injuries of traffic accidents. The least acceleration to the head of the child was under the angle of 45°. The highest acceleration to the head of the child was under the angle of 15°. Highest and lowest displacements were observed at X and Y directions. Abstract: It has been shown that annually around 1250 children younger than 15 years old die in traffic accident. The number of children who also injured as a consequence of car accidents is noticeably higher. According to the ECE-R44 regulation the safety of children in the cars, the use of a child safety seat (CSS) is highly recommended. Using a CSS would dramatically diminish the injuries of traffic accidents. However, the posture, especially the angle, of a child when seating on a seat may also affect the amount of injury occurs during the accident. It has been revealed that during the accident only few children remained seated in the standard position, and most of them whether slouched or slanted and turned their head to the side-support of the CSS. Extreme positions, such as leaning forward, escaping from the harness or holding feet were also observed. This study aimed to perform a finite element (FE) study to figure out what angle of seating would result in the least amount of injury to the child head in a typical car crash under the speed of 47 km/h. To do that, a 1.5 years old child dummy (a dummy representing the anthropometry of a 1.5 years old child) has been accommodated on a seat under the angles of 15°, 30°, and 45°. The results revealed. The resulted displacements in the head after the accident were also calculated at X, Y, and Z directions. The results in this regard indicated a higher displacement at X direction whereas the lowest one was seen at Y direction. The results have implications not only for understanding the amount of injury to the child head after the accident under different seating angles, but also for giving an insight to the CSS industries and families to choose the right seating posture for the child in the car to reduce the severity of injury.